Psychometric Properties of the Modified Persian Version of Adverse Childhood Experience Questionnaire for Athletes - Setareh Deinali; Rokhsareh Badami; Zohreh Meshkati; Sahar Faeghi (Vesnu Publications, 2020)
Introduction: The Adverse Childhood Experience (ACE) questionnaire is a self-administrable outcome tool designed to measure adverse childhood experiences. The aim of this study is to translate the ACE questionnaire into Persian and cross-culturally adapt it to athletes.Materials and Methods: The English version of the 10-item ACE was translated into Persian and completed by a sample of 210 athletes along with Childhood Trauma Questionnaire (CTQ). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to evaluate the validity. Additionally, to measure reliability, Cronbach's alpha and split-half coefficients were used. Convergent validity was also measured using Pearson's correlation coefficient.Results: The validity of the Persian version of the CAE questionnaire was confirmed. The reliability values obtained in term of Cronbach's alpha and split-half coefficients were higher than 0.7. The correlation between ACE and CTQ was positive (r = 0.68, P < 0.001).Conclusion: The Persian version of ACE is a reliable and valid measure in athletes.